2011
DOI: 10.1177/0146167211411723
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes as Justifications of Prejudice

Abstract: Three experiments investigate how stereotypes form as justifications for prejudice. The authors created novel content-free prejudices toward unfamiliar social groups using either subliminal (Experiment 1, N = 79) or supraliminal (Experiment 2, N = 105; Experiment 3, N = 130) affective conditioning and measured the consequent endorsement of stereotypes about the groups. Following the stereotype content model, analyses focused on the extent to which stereotypes connoted warmth or competence. Results from all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 34 publications
3
60
0
2
Order By: Relevance
“…In order to do this, we needed to select a group that American participants would have little familiarity with. Past research has shown that American undergraduates are very unfamiliar with the European nation of Slovenia (Crandall, Bahns, Warner, & Schaller, ). A pretest with eight students at the researchers' university was consistent with this finding that students had a mean familiarity of 1.63 ( SD = 0.52) with Slovenia on scale 1 (very unfamiliar) to 7 (very familiar).…”
Section: Studymentioning
confidence: 99%
“…In order to do this, we needed to select a group that American participants would have little familiarity with. Past research has shown that American undergraduates are very unfamiliar with the European nation of Slovenia (Crandall, Bahns, Warner, & Schaller, ). A pretest with eight students at the researchers' university was consistent with this finding that students had a mean familiarity of 1.63 ( SD = 0.52) with Slovenia on scale 1 (very unfamiliar) to 7 (very familiar).…”
Section: Studymentioning
confidence: 99%
“…Furthermore, evidence suggests that stereotypes can act to justify prejudice and discrimination (Crandall, Bahns, Warner et al, 2011;Devine, 1989;Rutland and Brown, 2001), which may also add to any stigma that people may face. Self-stigmatisation involves a process where people are both aware of and agree with group stereotypes, and then apply these stereotypes to themselves (Corrigan, Bink, Schmidt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A racist, when in contact with an individual who does not fit her stereotypes, would surely find it easier to classify the individual as an exceptional case rather than revise her racial stereotypes. Even when these counterexamples to her beliefs become increasingly common, stereotypes are extremely resistant to change (Rothbart and Park 1987;Schneider 2004;Crandall et al 2011). This, of course, fits very well with a naturalized epistemology in which anything may in fact be held true "come what may."…”
Section: Idealization Dogmatism and Belief Changementioning
confidence: 81%
“…Even when these counterexamples to her beliefs become increasingly common, stereotypes are extremely resistant to change (Rothbart and Park ; Schneider ; Crandall et al. ). This, of course, fits very well with a naturalized epistemology in which anything may in fact be held true “come what may.” But in that case, it is not so promising from an anti‐oppressive point of view.…”
Section: Idealization Dogmatism and Belief Changementioning
confidence: 99%